An update on formaldehyde adulteration in food: sources, detection, mechanisms, and risk assessment - Rahman, Md. Bokthier; Hussain, Monayem; Kabiraz, Meera Probha; Nordin, Noordiana; Siddiqui, Shahida Anusha; Bhowmik, Shuva; Begum, Mohajira (Elsevier BV, 2023)
Formaldehyde is added illegally to food to extend its shelf life due to its antiseptic and preservation properties. Several research has been conducted to examine the consequences of adulteration with formaldehyde in food items. These findings suggest that adding formaldehyde to food is considered harmful as it accumulates in the body with long-term consumption. In this review includes study findings on food adulteration with formaldehyde and their assessment of food safety based on the analytical method applied to various geographical regions, food matrix types, and their sources in food items. Additionally, this review sought to assess the risk of formaldehydetainted food and the understanding of its development in food and its impacts on food safety in light of the widespread formaldehyde adulteration. Finally, the study would be useful as a manual for implementing adequate and successful risk assessment to increase food safety